Characteristics of Patients Returning to Work After Brain Tumor Surgery - Schiavolin, Silvia; Mariniello, Arianna; Broggi, Morgan; Acerbi, Francesco; Schiariti, Marco; Franzini, Angelo; Di Meco, Francesco; Ferroli, Paolo; Leonardi, Matilde (Frontiers in Human Neuroscience, 2021)
Objective: To investigate the differences between patients returning to work and those who did not after brain tumor surgery. Methods: Patients were evaluated before surgery and after 3 months. MOCA, TMT-A and TMT-B, ROWL-IR and ROWL-DR, F.A.S tests, and KPS were used to assess cognitive status, attention and executive functions, memory, word fluency, and functional status. Patient reported outcome measures (PROMs) used to evaluate emotional distress and disability were HADS and WHODAS-12. Clinical and work related variables, PROMs and cognitive tests were compared using chi square, t-test or Mann-Whitney U test. Results: 60 patients were included. Patients returning to work were 61.3% and 31.0% among people with meningioma and glioma respectively. They reported lower postoperative disability and lesser home to work travel time. Patients with meningioma also showed better preoperative and postoperative attention and executive functions, better postoperative functional and cognitive status and lower frequency of treatments. Conclusions: These variables should be considered in clinical context to plan interventions for people who need support during return to work, and in future research to investigate preoperative and postoperative predictive factors of going back to work.